Spatial Scaling Patterns of Functional Diversity - Alirezazadeh, Saeid; Borges, Paulo A. V.; Cardoso, Pedro; Gabriel, Rosalina; Rigal, François; Borda-de-Água, Luís (Frontiers in Ecology and Evolution, 2021)
Ecology, biogeography and conservation biology, among other disciplines, often rely on species identity, distribution and abundance to perceive and explain patterns in space and time. Yet, species are not independent units in the way they interact with their environment. Species often perform similar roles in networks and their ecosystems, and at least partial redundancy or difference of roles might explain co-existence, competitive exclusion or other patterns reflected at the community level. Therefore, considering species traits, that is, the organisms’ functional properties that interact with the environment, might be of utmost importance in the study of species relative abundances. Several descriptive measures of diversity, such as the species-area relationship (SAR) and the species abundance distribution (SAD), have been used extensively to characterize the communities and as a possible window to gain insight into underlying processes shaping and maintaining biodiversity. However, if the role of species in a community is better assessed by their functional attributes, then one should also study the SAR and the SAD by using trait-based approaches, and not only of taxonomic species. Here we merged species according to their similarity in a number of traits, creating functional units, and used these new units to study the equivalent patterns of the SAR and of the SAD (functional units abundance distributions - FUADs), with emphasis on their spatial scaling characteristics. This idea was tested using data on arthropods collected in Terceira islands, in the Azorean archipelago. Our results showed that diversity scales differently depending on whether we use species or functional units. If what determines species communities’ dynamics is their functional diversity, then our results suggest that we may need to revaluate the commonly assumed patterns of species diversity and, concomitantly, the role of the underlying processes.